2003
DOI: 10.2466/pms.2003.96.3c.1223
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Age with Time of Day and Mental Load in Different Cognitive Tasks

Abstract: Extensive research has demonstrated that shiftwork produces deleterious effects on health because of the desynchrony it induces in the biological clock. The problem is even more crucial for older workers who present, in addition, various decrements in their cognitive functioning, particularly on attention and memory. The present study assessed whether age was related to task complexity as a function of time of day and time-on-task in a rapid rotating work-rest schedule. 24 subjects (12 juniors: 20-30 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
(7 reference statements)
1
18
0
Order By: Relevance
“…Additionally, a previous study with adults found that circadian timing influences planning performance only when the level of difficulty was high, even though this was in disagreement with a previous study (Bonnefond et al 2003). One of the few studies investigating more complex EFs (i.e.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Additionally, a previous study with adults found that circadian timing influences planning performance only when the level of difficulty was high, even though this was in disagreement with a previous study (Bonnefond et al 2003). One of the few studies investigating more complex EFs (i.e.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies found that circadian timing influences planning performance only when the level of difficulty was high (Bonnefond et al 2003). Further data indicate that task difficulty can be successfully manipulated in inhibitory control tasks (Lindqvist & Thorell 2009).…”
mentioning
confidence: 81%
“…60 However, this recommendation is not supported by the studies in women 57,58 or those in men. 61,62 Performance For optimal productivity, workers need to be quick and efficient to minimize workplace errors, but a decrement in performance and a rise in accidents occur with sleep deprivation. Table 3 is a synopsis of the literature in this area.…”
Section: Shift Work Sleep and Agementioning
confidence: 99%
“…Furthermore, the authors previously reported several factors associated with sleepiness and performance during the night shift (Zion, Drach‐Zahavy, & Shochat, ; Zion & Shochat, ). Older shift workers were more vulnerable to the negative impacts of night work on cognitive performance (Bonnefond et al, ; Bonnefond, Rohmer, Hoeft, Muzet, & Tassi, ; Tadinac, Sekulić, Hromatko, Mazul‐Sunko, & Ivancić, ), whereas younger workers reported increased sleepiness (Bonnefond et al, ; Härmä, Sallinen, Ranta, Mutanen, & Müller, ; Zion et al, ). In addition, morning chronotypes preferred going to bed early and experienced high levels of sleepiness during night shifts (Gamble et al, ; Saksvik, Bjorvatn, Hetland, Sandal, & Pallesen, ; Seo, Matsumoto, Park, Shinkoda, & Noh, ; van de Ven et al, 2).…”
Section: Introductionmentioning
confidence: 99%